Analysis of the vulnerability of IT system users to a phishing attack - Grzebielec, Szymon (Journal of Computer Sciences Institute, 2020)
This article presents an analysis of users’ vulnerability to phishing attacks. The study was carried out using a self-prepared attack. A phishing attack was carried out on a group of 100 people. The subjects were divided into two groups of 50 people. The first group was attacked from a private, trusted account. The second group was attacked from a foreign email address. The attacked people were asked to complete the survey, its results and conclusions are presented in this article.